Avaliação físico-química e microbiológica de leite pasteurizado tipo C distribuído em programa social governamental - Regina Marcia Bahia Paiva (2007)
The microbiological and physical-chemical quality of 151 pasteurized type C milk samplesdistributed by a governmental program in Minas Gerais state was analyzed. Milk qualitywas also traced to the dairies, in accordance to the type of inspection, as well as to theproduce regions and season. For the microbiological analyses, means were: 6.09 x 101MPN/mL and 2.47 x 101 MPN/mL for coliforms at 30°C and 45°C, respectively; 1.38 x 105CFU/mL for counting of aerobic mesophilic bacteria; and 1.31 x 105 CFU/mL and 2.54 x104 CFU/mL for counting of Staphylococcus spp. and Staphylococcus aureus, respectively.Salmonella spp. was identified in 121 (2.48%) samples. For the physical-chemical analyses,means were: 1.031 for density at 15°C, 12.40% for total solids content, 3.60% for fat,8.80% for non-fat solids, 15.32°D for titratable acidity, and 0.525°H for freezing point.Mean of water added to milk was 2.4%. Positive result for alkaline phosphatase activitywas observed in 23.18% samples and 22.52% presented negative activity oflactoperoxidase. Difference (p>0.05) was not observed among the dairy industries underdifferent levels of inspection, and among different regions the State for the microbiologicalaspects; however, difference was observed (p<0.05) for the majority of the physicalchemicalaspects. Difference was not observed among the seasons of the year concerningmicrobiological and physical-chemical aspects. It was concluded that the pasteurized milkdistributed by the governmental program had unsatisfactory quality; deficient compositionand can represent a potential risk to the health of the consumers